Controlling epidemics with mathematical and machine learning models - Varghese, Abraham ca. 20./21. Jh; Lacap, Eduardo M. ca. 20./21. Jh; Sajath, Ibrahim ca. 20./21. Jh; Kumar, Kamal 1980-; Kolamban, Shajidmon ca. 20./21. Jh (Advances in computational intelligence and robotics (ACIR) book series, 2023)
The objective of this book is to make mathematical models for epidemical diseases, especially Covid-19, focusing on quarantine, isolation and vaccine effect for the control of the disease and providing simulation of the model to be done with the help of python/matlab.